The Purchase Intention of E-Commerce Live Broadcast Consumers and Its Influencing Factors Based on SOR Theory - Mediated by Perceived Value and Consumption Release - Fang, Wang; Kumboon, Buraporn; Prakthayanon, Suchart; Karaweak , Sirachaya (International Journal of Multidisciplinary in Management and Tourism, 2024)
In the current situation, the internet can be accessed easily and conveniently. Organizations have adapted to reach consumers quickly, including selling products and services to customers. This article aimed to study 1) the impact of the incentive mechanism, perceived value, demand release, and purchase intention of live-streaming consumers on live-streaming e-commerce platforms and 2) the factors of motivation and purchase intent of consumers on live e-commerce platforms. This is mixed research The analysis of basic data adopts content such as frequency, percentage, mean, standard deviation, etc. and the second part is model analysis, which uses structural equation statistical analysis. The research results were found as follows; 1. The results showed that Most of the respondents were female (62.26 %), aged 18-22 (68.55 %), had a bachelor's degree (84.28 %), and had an average monthly income of less than 230 yuan. (72.33 %). 2. The results showed that the motivation factor and the consumer purchase intent factor positively affected consumers' online purchases through live streaming.